1991
DOI: 10.1002/1097-0142(19910701)68:1<56::aid-cncr2820680111>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Continuous intra-arterial administration of recombinant interleukin-2 in low-stage bladder cancer. A phase IB study

Abstract: Toxicity and clinical effects of intra-arterial (IA) continuous infusion of recombinant interleukin-2 (rIL-2) were evaluated in twelve patients with low-stage transitional cell carcinoma (TCC) of the bladder (T1NOMO; G1 to G2). rIL-2 dosages were escalated from 18 x 10(3) to 18 x 10(6) IU/m2/d in four groups of three patients. After two 5-day courses, separated by a 48-hour interval, evaluation of clinical response and transurethral resection (TUR) were carried out. World Health Organization (WHO) Grade 3 toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Multiple murine studies have demonstrated that systemic administration of IL-2, with or without BCG, can significantly decrease tumor size, suppress tumor growth, and improve mean survival [7173]. A small clinical study investigating systemic IL-2 administration effects on low-stage bladder cancer found a complete and partial response rate in 5 of 12 patients, though 2 patients discontinued therapy due to toxicity [74]. The poor side effect profile of systemic IL-2 administration subsequently prompted a shift to utilize IL-2 as an intravesical therapy.…”
Section: Interleukin-2mentioning
confidence: 99%
“…Multiple murine studies have demonstrated that systemic administration of IL-2, with or without BCG, can significantly decrease tumor size, suppress tumor growth, and improve mean survival [7173]. A small clinical study investigating systemic IL-2 administration effects on low-stage bladder cancer found a complete and partial response rate in 5 of 12 patients, though 2 patients discontinued therapy due to toxicity [74]. The poor side effect profile of systemic IL-2 administration subsequently prompted a shift to utilize IL-2 as an intravesical therapy.…”
Section: Interleukin-2mentioning
confidence: 99%
“…Although the role of such mechanisms in the rejection of IL-2 gene-transduced bladder cancer cells has not been explored in the present study, an even more interesting support to their potential relevance in this tumour model comes from our earlier experience with intraarterial or intravesical rIL-2 treatment in patients with superficial transitional cell carcinoma of the bladder (Tubaro et al, 1991(Tubaro et al, , 1995Velotti et al, 1991aVelotti et al, , 1991b. In these clinical trials we observed a significant increase in the inflammatory response at the tumour site, with evident infiltration of tumour stroma and neoplastic epithelium by activated (CD25 + /HLA-DR + ) T-cells, macrophages and both eosinophil and PMN.…”
Section: Discussionmentioning
confidence: 66%